Nonresponse bias in public leadership research: an empirical assessment. Issue 3 (24th March 2021) - Vogel, Dominik; Jacobsen, Christian B.
Abstract: Self-reported measures of leadership are widely used in public management research, but nonresponse bias poses a threat to the validity of these data. Although this measurement problem is acknowledged, it has received limited empirical attention because nonresponse bias is inherently challenging to study. To address this issue, we examine nonresponse bias among public managers by analyzing multilevel surveys of managers and employees in which we can compare employee ratings of leadership for both responding and nonresponding managers. Using 16, 531 employee responses spread over six data sets from three countries, we find only limited evidence of nonresponse bias in managers' self-reported leadership. Additional Bayesian analyses indicate that—overall—the data are indicative of the absence of substantial nonresponse bias. However, the results vary between data sets and call for more research on nonresponse bias in leadership research.